2002
DOI: 10.1300/j013v36n02_03
|View full text |Cite
|
Sign up to set email alerts
|

Environmental, Policy, and Cultural Factors Related to Physical Activity in Well-Educated Urban African American Women

Abstract: The purpose of this qualitative study was to identify environmental, policy, and cultural predictors of physical activity in urban African American women living in Baltimore, MD. Thirty-nine mostly well-educated women participated in eight focus group discussions, five for women aged 36 to 50 years and three for women 20 to 35 years of age. Transcripts were analyzed using QSR NUD*IST qualitative software, and themes were identified. The discussions identified numerous opportunities and barriers for physical ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 8 publications
6
58
0
2
Order By: Relevance
“…Furthermore, younger rather than older AAW, and those with higher education and income levels reported increased participation in PA for weight control and vanity rather than to avoid ill-health (Eyler, et al, 2003;Young, He, Harris, & Mabry, 2002) Cultural factors are reported to hinder obesity-related intervention among AAs.…”
Section: Behavioral Factors Physical Activitymentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, younger rather than older AAW, and those with higher education and income levels reported increased participation in PA for weight control and vanity rather than to avoid ill-health (Eyler, et al, 2003;Young, He, Harris, & Mabry, 2002) Cultural factors are reported to hinder obesity-related intervention among AAs.…”
Section: Behavioral Factors Physical Activitymentioning
confidence: 99%
“…However, AAW did report increased motivation for PA when they exercised with a friend or in groups (Young et al, 2002). The latter was highly favored in women who attended religious establishments; some reported that praying and spiritual guidance were important for weight loss, and health-related activities were important for sustaining their weight (Davis et al, 2005a).…”
Section: Behavioral Factors Physical Activitymentioning
confidence: 99%
See 3 more Smart Citations